The reproductive system: gametogenesis and the ovarian cycle - Garside, Victoria (Henry Stewart Talks, 2024)
Gametogenesis process, Spermatogenesis stages, Oogenesis stages, Hormonal control of spermatogenesis, Hormonal control of ovarian and uterine cycles, The menstrual cycle